Serum Testosterone and Cortisol Concentrations After Single-Dose Administration of 100-Mg Transdermal Testosterone in Healthy Men - Puiu, Andrei A.; Radke, Sina; Votinov, Mikhail; Habel, Ute; Herpertz-Dahlmann, Beate; Turetsky, Bruce; Konrad, Kerstin (Frontiers in Pharmacology, 2019)
The growing interest in testosterone’s effects on men’s social behaviours, in particular aggressive, risk-taking, or status maintenance behaviours, is accompanied by a paucity of dose-dependent pharmacokinetic data. Examining the neurophysiological effects of transdermal testosterone typically includes a 4h delay before further brain-behaviour measurements. Nevertheless, high heterogeneity regarding the timing of follow-up measurements and dosage remains. In a double-blind placebo-controlled design, we examined the short-term pharmacokinetic profile of 100mg transdermal testosterone (Testotop®) to determine the optimal time for detecting testosterone-mediated effects. Across two studies, thirty-five healthy men received a single dose of testosterone and placebo in two separate sessions. In study one (n = 16), serum testosterone and cortisol were assessed serially every 30 minutes up to two hours post-treatment. In study two (n = 19), we assessed serum testosterone and cortisol at baseline, two hours, and 4.15 h (255 minutes) post-treatment. Relative to baseline and placebo, transdermal testosterone significantly increased total serum testosterone concentrations 90 minutes post-treatment, reaching maximum concentration between two and three hours post-treatment. Albeit elevated, serum testosterone levels gradually decreased between two and four hours following treatment. Transdermal testosterone did not suppress cortisol release. Instead, cortisol concentrations decreased according to cortisol’s known circadian rhythm. Unlike previous findings showing significant testosterone concentration increases as soon as 60 minutes and as late as three hours post 150mg testosterone treatment, our 100mg testosterone manipulation significantly increased testosterone concentrations 90 minutes following treatment. These pharmacokinetic data are important in facilitating the optimization of timing parameters for future testosterone challenge studies.